International Conference on Intelligent Computing and Applications ICICA 2016 - Dash, Subhransu Sekhar; Das, Swagatam; Panigrahi, Bijaya Ketan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The book is a collection of best papers presented in International Conference on Intelligent Computing and Applications (ICICA 2016) organized by Department of Computer Engineering, D.Y. Patil College of Engineering, Pune, India during 20-22 December 2016. The book presents original work, information, techniques and applications in the field of computational intelligence, power and computing technology. This volume also talks about image language processing, computer vision and pattern recognition, machine learning, data mining and computational life sciences, management of data including Big Data and analytics, distributed and mobile systems including grid and cloud infrastructure.
Preface -- About the editors -- Table of contents -- 60 chapters -- Author Index.
Keywords: Computational intelligence; Signal processing; Data mining; Computational Intelligence; Signal, Speech and Image Processing; Data Mining and Knowledge Discovery